Investigation on the vertical distribution and transportation of PM2.5 in the Beijing-Tianjin-Hebei region based on stereoscopic observation network. (1st February 2023) - Sun, Tingting; Zhang, Tianshu; Xiang, Yan; Fan, Guangqiang; Fu, Yibin; Lv, Lihui
Abstract: In recent years, the regional PM2.5 pollution occurred frequently, especially in the Beijing-Tianjin-Hebei (BTH) region, China. Understanding the characteristics of PM2.5 pollution and its traceability within the boundary layer is necessary to better implement effective emission control strategies. In this study, we used the observed data from stereoscopic observation network, the simulated concentrations and regional transport of PM2.5 from CMAQ-ISAM model, combined with the PM2.5 transport flux, to investigate a comprehensive analysis of the PM2.5 pollution over the BTH region during January 18–31, 2018. The results showed that there were two pollution episodes (E1 and E3) and two clean episodes (E2 and E4) during the research period. The PM2.5 pollutants at the surface layer in Beijing were dominated by the contributions from local source, accounting for 55.63% in E1, 62.20% in E2, 58.83% in E3, and 65.94% in E4, respectively. The pollutant transport from the southern and southwestern pathways played the important role in controlling the PM2.5 pollution levels in Beijing city, the height of the pollutant transport was mainly concentrated from 0.5 to 2.0 km, and the maximum transport flux reached 972 μg/(m 2 ·s) during the pollution episodes. The transport from eastern and southeastern pathways were significant within 1.0 km under the prevailing wind, the maximum transport flux reached 629 μg/(m 2 ·s). During the cleaning episodes, the pollution transport of PM2.5 within the boundary layer mainly came from northern and southwestern pathways, with a maximum transport flux of 482 μg/(m 2 ·s). Overall, the pollution process of Beijing is not only from local emissions, but also affected by regional transport during the research period. Therefore, it is necessary to control local emissions and strengthen regional-scale collaborations to reduce regional pollution events. Highlights: Characteristics of the regional distribution of aerosol particles in the BTH region were observed by lidar network. During the research period, the local source was the main contributor to the air pollution in Beijing at the surface layer. The pollutant transport from the southwestern pathway played the important role in controlling the PM2.5 pollution levels in Beijing.